Cool and warm ionotropic receptors control multiple thermotaxes in Drosophila larvae - Omelchenko, Alisa A.; Bai, Hua; Spina, Emma C.; Tyrrell, Jordan J.; Wilbourne, Jackson T.; Ni, Lina (Frontiers in Molecular Neuroscience, 2022)
Animals are continuously confronted with different rates of temperature variation. The mechanism underlying how temperature-sensing systems detect and respond to fast and slow temperature changes is not fully understood in fly larvae. Here, we applied two-choice behavioral assays to mimic fast temperature variations and a gradient assay to model slow temperature changes. Previous research indicates that Rhodopsin 1 (Rh1) and its phospholipase C (PLC) cascade regulate fast and slow temperature responses. We focused on the ionotropic receptors (IRs) expressed in dorsal organ ganglions, in which dorsal organ cool-activated cells (DOCCs) and warm-activated cells (DOWCs) rely on IR-formed cool and warm receptors to respond to temperature changes. In two-choice assays, both cool and warm IRs are sufficient for selecting 18°C between 18 and 25°C but neither function in cool preferences between 25 and 32°C. The Rh1 pathway, on the other hand, contributes to choosing preferred temperatures in both assays. In a gradient assay, cool and warm IR receptors exert opposite effects to guide animals to 25°C. Cool IRs drive animals to avoid cool temperatures, whereas warm IRs guide them to leave warm regions. The Rh1 cascade and warm IRs may function in the same pathway to drive warm avoidance in gradient assays. Moreover, IR92a is not expressed in temperature-responsive neurons but regulates the activation of DOWCs and the deactivation of DOCCs. Together with previous studies, we conclude that multiple thermosensory systems, in various collaborative ways, help larvae to make their optimal choices in response to different rates of temperature change.